Pro-Quality Cost Accounts in a Time of Sustainable Development - Renata Biadacz (International Journal of Supply Chain Management, 2019)
Enterprises that operate nowadays and want to maintain a competitive advantage on the market, face numerous challenges. Problems of contemporary world, in particular progressive degradation of natural environment, have forced business entities to conduct their operations in a socially responsible manner, in other words, in line with principles of sustainable development. Corporate social responsibility in this field can be defined as overall activities of a company aimed at implementing this concept within the framework of quality policy. Achieving goals and performing tasks related to implementation of the concept of corporate social responsibility, in accordance with continuous improvement of quality effectiveness, can be supported by pro-quality cost accounting. Broadly understood quality management exploits information from accounting system. Quality costing is considered to be the most important element of quality management system. Undoubtedly it plays a major role in establishing a sustainable development policy and related initiatives, as it provides a framework for implementation of corporate social responsibility (CSR) strategies at all levels of organization's management. The main reason for choosing this kind of research problem was growing importance of information about quality costs in the era of corporate social responsibility, which has been observed recently. Therefore, the aim of framework is to present a nature and significance of quality costing and pro-quality cost accounting in the management of a modern enterprise. To achieve this purpose, it was necessary to use literature analysis of the subject. Assumed objective of the work was achieved through broader description of the concept of sustainable development, discussion of the essence of quality costing, thorough analysis of pro-quality cost accounts as well as presentation of pilot studies on the use of quality costing models and quality cost accounting in enterprises from the SME group existing in Poland. Conducted research allowed to identify existing research gap, which refers to the context of a wider application of quality costing as an integral part of modern strategic management accounting systems.